Fit for fight - self-reported health in military women: a cross-sectional study - Elin Anita Fadum; Leif Åge Strand; Monica Martinussen; Laila Breidvik; Nina Isaksen; Einar Borud (BMC, 2019)
Abstract Background Substantial research has found that women assess their health as poor relative to men, but the reasons for this are not fully understood. Military women are characterised by good health and the ability to work in an archetypically male culture. Thus, studies on the gender pattern of self-reported health in military personnel could generate hypotheses for future research on the possible associations between gender and health. However, such studies are rare and limited to a few countries. The aim of this study was to examine self-reported physical and mental health in Norwegian military women. Methods We compared responses on self-reported health of 1068 active duty military women in Norway to those of active duty military men (n = 8100). Further, we compared the military women to civilian women working in the Norwegian Armed Forces (n = 1081). Participants were stratified into three age groups: 20-29; 30-39; and 40-60 years. We used Pearson Chi-square tests, Students t-tests and regression models to assess differences between the groups. Results The military women in our study reported physical illness and injuries equal to those of military men, but more military women used pain relieving and psychotropic drugs. More military women aged 20-29 and 30-39 years reported mental health issues than military men of the same age. In the age group 30-39 years, twice as many military women assessed their health as poor compared to military men. In the age group 40-60 years, more military women than men reported musculoskeletal pain. Military women used less smokeless tobacco than military men, but there were few differences in alcohol consumption and smoking. Military women appeared to be more physically healthy than civilian women, but we found few differences in mental health between these two groups. Conclusion Most military women reported physical symptoms equal to those of military men, but there were differences between the genders in mental health and drug use. More favourable health compared to civilian women was most evident in the youngest age group and did not apply to mental health.